Ecosystem service of carbon stored in coffee plantations under shade in agroforestry systems - Valdés-Velarde, Eduardo; Vázquez-Domínguez, Laura Patrícia; Tinoco-Rueda, Juan Ángel; Sánchez-Hernández, Rufo; Salcedo-Pérez, Salcedo-Pérez; Lagunes-Fortiz, Erika (Revista Mexicana de Ciencias Agrícolas, 2022)
Coffee agroforestry systems (AFSs) have a high potential in carbon (C) sequestration thanks to the great diversity of woody species used as shade. The objective of this study was to evaluate the potential for carbon sequestration in aerial plant biomass, plant litter and soil matter at different soil depths in five different coffee AFSs in the coffee-growing region of Huatusco, Veracruz, Mexico. The agroforestry systems studied were: in full sun (03.PSC-MZ, 04.PSC-ZI), specialized (05.ESP-MZ, 06.ESP-MZ, 07.ESP-CH) and were compared with a cloud forest (02.BMM-CH) and a paddock (01.POT-TH). The AFS with the highest C content in aerial biomass, estimated with allometric equations, was 05.ESP-MZ, with 373.75 Mg ha-1, followed by 07.ESP-CH with 231.88 Mg ha-1, 04.PSC-ZI with 123.96 Mg ha-1, 03.PSC-MZ with 61.08 Mg ha-1, 06.ESP-MZ with 45.95 Mg ha-1, 02.BMM-CH 456.64 Mg ha-1 and 01.POT-TH 3.14 Mg ha-1. Regarding the total organic C, the 05.ESP-MZ system obtained the highest value with 477.54 Mg ha-1 and the 06.ESP-MZ the lowest with 108 Mg ha-1. The implementation and conservation of coffee AFSs is vital since it contributes to mitigating the negative environmental impact such as CO2 emissions into the atmosphere, soil compaction and loss of biodiversity in flora and fauna that other production systems have caused.